(untitled) (Research, Society and Development, 2022)
Exploratory and descriptive research that sought to explore the relationship between guided physical activity and the mental health of students and health professionals. Research carried out in reliable databases, with the descriptors health students, health professionals, mental health and physical activity oriented. Health students showed fatigue, tiredness, difficulties in adapting to the academic environment, lack of time to dedicate to leisure and personal life, obsession with technical work, excessive personal demands, frustrations related to the course and difficulties inherent in the teacher-student relationship and professional-patient, aggravated by economic stressors, changes in daily habits and academic delays due to the epidemic. Recent data were added to the existing ones on the prevalence of depression, anxiety, stress and high levels of problems related to mental health among health professionals during the pandemic who, during the Covid-19 pandemic, acted under pressure due to excess of work, lack of supplies, greater exposure to patients’ negative emotions, worries, anxiety and fear of being contaminated by the virus and also transmitting it to their families. Physical activity and well-being can have substantial impacts on human health and the effective practice of daily physical exercise is beneficial to physical and mental health, and can reduce symptoms of anxiety and stress caused by social isolation. There are important gaps in knowledge about the subject of mental health care for students and health professionals, and the information collected and systematized here can provide important support for research in this area.